2006
DOI: 10.4049/jimmunol.176.9.5199
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Hemopoietic Stem Cells in the Adult Human Small Intestine

Abstract: The concept of lymphoid differentiation in the human gastrointestinal tract is controversial but is the focus of this study, which examined adult human small intestinal tissue for the presence of CD34+CD45+ hemopoietic stem cells (HSCs) and lymphoid progenitors. Flow cytometry demonstrated that over 5% of leukocytes (CD45+ cells) isolated from human gut were HSCs coexpressing CD34, a significantly higher incidence than in matched peripheral blood or control bone marrow. HSCs were detected in cell preparations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 38 publications
0
29
0
1
Order By: Relevance
“…However, liver and intestinal hematopoietic progenitors may differ in their multilineage differentiation potential. Although liver hematopoietic stem cells can give rise to multiple lineages, including lymphoid (44) and myeloid (45) cells, human gut-derived progenitors cells are almost exclusively lymphoid (CD7 positive) (46) and therefore only able to generate T cells (47). Consistent with this observation, in contrast to liver and multivisceral recipients, liver-free intestinal transplant recipients never displayed myeloid macrochimerism in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, liver and intestinal hematopoietic progenitors may differ in their multilineage differentiation potential. Although liver hematopoietic stem cells can give rise to multiple lineages, including lymphoid (44) and myeloid (45) cells, human gut-derived progenitors cells are almost exclusively lymphoid (CD7 positive) (46) and therefore only able to generate T cells (47). Consistent with this observation, in contrast to liver and multivisceral recipients, liver-free intestinal transplant recipients never displayed myeloid macrochimerism in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Another example of extramedullary microenvironment specific lymphoid development is found in gastrointestinal mucosa, where extensive expression of Notch and their ligands are found [50]. The human small intestine is a site of CD34 + CD7 + lymphoid precursor development, not generally present in the circulation, suggesting that the gut may be an important site of early lymphoid differentiation [51]. These findings support the notion that Notch ligand expressing tissues play a role in NK cell differentiation and ultimately in the process of NK cell education.…”
Section: Discussionmentioning
confidence: 99%
“…24 Similar cells have subsequently been described in mucosa-associated lymphoid tissue in the gut. 25,26 This selective enrichment of both CD34 ϩ CD45RA ϩ pre-NK cells and CD56 bright NK cells within SLT relative to BM or blood, along with an abundance of dendritic cells (DCs) and other antigen presenting cells (APCs) that express membranebound IL-15, 27 which is required for NK-cell maturation, [28][29][30] suggested that SLT may be a site for NK-cell development in vivo. Indeed, a search in SLT for phenotypically and functionally distinct cell populations that represent stages along the NKcell developmental pathway from CD34 ϩ CD45RA ϩ HPCs to CD3 Ϫ CD56 bright NK cells in situ was successfully undertaken (Figure 2).…”
mentioning
confidence: 99%